Aplikasi Pupuk Kotoran Kelinci Dan Pupuk Anorganik Pada Tanaman Jagung Pulut (Zea Mays Ceratina L.) - Rahmatika, Widyana; Fitriyah, Nur; D Andayani, Retno; Handayani, Tri; Novitasari, Dian (JURNAL ILMIAH AGRINECA, 2024)
One of the most popular corn varieties is pulut corn, because it has a savory, fluffier taste and an attractive appearance that is different from corn in general. The continuous application of inorganic fertilizers without the addition of organic fertilizers can have an impact on reducing soil quality physically, chemically and biologically which causes the growth of pulut corn plants to be not optimal. To overcome this, it is necessary to input organic fertilizer. This study aimsto determine the effect of rabbit manure treatment on the growth and yield of corn pulut plants (Zea mays ceratina. L.). Tofind out the effect of NPK fertilizer dose treatment on the growth and yield of pulut corn plants (Zea mays ceratina. L.). The implementation of this research starts from October 10, 2022 to January 7, 2023. This research was conducted at the UNISKA Integrated Field Laboratory, Rejomulyo Village, Kediri City District, with an altitude of 67 meters above sea level. The average morning temperature is 27.22°C and the afternoon is 34.36°C with an average morning humidity of  86.07 and an afternoon of 49.32. Sandy loam soil type with an acidity level of 6.7 pH. This study used a Factorial Randomized Block Design (RBDF) with two factor. The first factor consists of two levels of rabbit fecal treatment i.e., K1 = solid rabbit manure (3.5 kg/plot) and K2 = liquid rabbit manure (40 ml/plant). The second factor is the dose of NPK fertilizer with 4 levels of treatment, namely, N0 = NPK fertilizer dose 0 gr / plant, N1 = NPK fertilizer dose 3 gr / plant, N2 = NPK fertilizer dose 6 gr / plant, N3 = NPK fertilizer dose 7 gr / plant. The data obtained from the observations on each observation variable are entered into the table to be carried out test F with the analysis of variance method (ANOVA) and further tested using the 5% BNT test. Based on the results of the study, there was no interaction between rabbit manure treatment and NPK fertilizer doses on the growth and yield of pulut corn plants (Zea mays ceratina. L.). However, each rabbit manure treatment and NPK fertilizer dose showed a noticeable influence on the growth and yield of the pulut corn crop (Zea mays ceratina. L.). On the treatment of rabbit witters exert a noticeable influence on the variables of observation of the number of leaves, plant height, and stem diameter. Whereas in the treatment of NPK fertilizer doses it had a significant effect on the observed variable number of leaves, plant height, stem diameter, cob length, cob diameter, and cob weight without the best husks shown in the treatment of NPK fertilizer 9 g/plant (N3) which was as much as 7.38 tons /Ha.